Morphophysiological responses and gene regulation of two bermudagrass cultivars differing in response to drought stress - Jia Jiang; Along Chen; Jiayi Qi; Xiashun Liu; Qianhan Zhao; Chen Wang; Tiantian He; Xueling Zheng; Wenjing Deng; Jingbo Chen; Dandan Li; Fuchun Xie; et al. (Chemical and Biological Technologies in Agriculture)
Abstract Bermudagrass (Cynodon dactylon) is a widely used warm-season turfgrass worldwide. However, bermudagrass often faces the challenges from drought stress in practical application. Selection and breeding of drought-tolerant cultivars of bermudagrass is crucial for thriving in arid environments. In this study, we employed two different drought-tolerant bermudagrass cultivars ‘Yangjiang’ and ‘Guanzhong’ to assess the morphology, physiology and transcriptome under various drought stress conditions. The outcomes unveiled that drought-tolerant ‘Guanzhong’ exhibited superiority in morphology, light utilization efficiency, relative water content, antioxidant and osmotic regulation capabilities compared to drought-susceptible ‘Yangjiang’. In addition, transcriptome sequencing showed that photosynthesis, amino acid metabolism, peroxisome and plant hormone signal transduction pathways were the key metabolic pathways of bermudagrass in response to drought stress. Compared to the drought-sensitive cultivar ‘Yangjiang’, the drought-tolerant ‘Guanzhong’ exhibited lower expression of AUX/IAA genes (negative regulators of auxin signaling), which reduces their inhibitory effect on auxin response factors (ARF), thereby enhancing auxin signaling efficiency to coordinate adaptive growth. Additionally, compared with ‘Yangjiang’, the down-regulated protein phosphatases (PP2C) in ‘Guanzhong’ weaken their suppression of SnRK2, resulting in heightened ABA signaling sensitivity. In comparison to ‘Yangjiang’, ‘Guanzhong’ displayed a higher IAA concentration and a lower ABA concentration under stress conditions, thus ensuring a more efficient utilization of water by minimizing stomatal aperture and reducing water evaporation. The results suggested that regulation of morphology, physiological metabolism and genes expression could contribute to drought tolerance in bermudagrass. Graphical Abstract